Vacuum infusion method for woven carbon/Kevlar reinforced hybrid composite - Hashim, N.; Majid, D. L.; Uda, N.; Zahari, R.; Yidris, N. (IOP Publishing, 2017)
The vacuum assisted resin transfer moulding (VaRTM) or Vacuum Infusion (VI) is one of the fabrication methods used for composite materials. Compared to other methods, this process costs lower than using prepregs because it does not need to use the autoclave to cure. Moreover, composites fabricated using this VI method exhibit superior mechanical properties than those made through hand layup process. In this study, the VI method is used in fabricating woven carbon/Kevlar fibre cloth with epoxy matrix. This paper reports the detailed methods on fabricating the hybrid composite using VI process and several precautions that need to be taken to avoid any damage to the properties of the composite material. The result highlights that the successfully fabricated composite has approximately 60% of fibres weight fraction. Since the composites produced by the VI process have a higher fibre percentage, this process should be considered for composites used in applications that are susceptible to the conditions where the fibres need to be the dominant element such as in tension loading.